Viral myocarditis: a prime example for endomyocardial biopsy-guided diagnosis and therapy - Van Linthout, Sophie (Curr Opin Cardiol, 2018)
PURPOSE OF REVIEW: Myocarditis is an inflammatory disease of the cardiac muscle mainly caused by viral infection. Due to the diverse clinical presentation of myocarditis, accurate diagnosis demands simultaneous histologic, immunohistochemical and molecular biological workup of endomyocardial biopsies (EMBs) as defined by the position statement of the Working Group on Myocardial and Pericardial Diseases of the European Society of Cardiology on myocarditis. RECENT FINDINGS: Endomyocardial biopsy-based analysis of viral transcriptional activity, mRNA expression, epigenetics and region-specific protein expression analysis via imaging mass spectrometry have led to the identification of novel potential diagnostic criteria, markers with prognostic value and therapeutic targets for the treatment of viral myocarditis, opening new avenues for novel therapies, including cell therapies, as well as the use of established treatment options, be it from other indications. SUMMARY: Under certain clinical scenarios EMB-based analysis is required to come to a tailored individualized therapy that improves symptoms and prognosis of patients with acute and chronic viral-driven cardiac inflammation.